A Analisis Kelayakan Isi Buku Bahasa Arab Kelas 7 Mts Kurikulum Merdeka Karangan Hasan Saefulloh - Annuari, Farida; Ilhami, Hamidi; Syamsudin Noor, Muhammad (UIN ANTASARI, 2025)
Arabic language learning in Indonesia has begun implementing the Merdeka Curriculum, which requires materials that align with students' needs. The book “Semangat Mendalami Bahasa Arab Kelas 7 MTs” by Hasan Saefulloh, published by Erlangga, is one of the instructional books designed for the Merdeka Curriculum. This resesarch aims to analyze the feasibility of listening (maharah istima’) and speaking (maharah kalam) materials in the book based on the standards set by the Agency for Education Standards, Curriculum, and Assessment (BSKAP). This research applies a qualitative descriptive with a library research method and data collection through documentation techniques. Data analysis uses content analysis with enhanced accuracy. The findings reveal that most of the listening and speaking materials meet the content feasibility standards, with only a few areas falling short. Overall, the content is considered good and suitable for use. However, further development is recommended, particularly in integrating technology and utilizing more up-to-date references.